S100B, Homocysteine, Vitamin B12, Folic Acid, and Procalcitonin Serum Levels in Remitters to Electroconvulsive Therapy: A Pilot Study - Maier, Hannah; Helm, Saskia; Toto, Sermin; Moschny, Nicole; Sperling, Wolfgang; Hillemacher, Thomas; Kahl, Kai G.; Jakubovski, Ewgeni; Bleich, Stefan; Frieling, Helge; Neyazi, Alexandra (Disease Markers, 2018)
Background: Electroconvulsive therapy (ECT) is one of the most effective treatment options for refractory depressed patients. To date, there are only a few predictors of response. Aim: The aim was to identify predictive biomarkers of remission to ECT on a molecular level. Methods: 11 patients suffering from a major depressive episode-according to the Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV)-underwent 10 ECT sessions. Blood samples were taken, and the depression severity was assessed before, one hour and 24 hours after sessions 1, 4, 7, and 10 using the Montgomery Asberg Depression Rating Scale (MADRS). A MADRS total score < 12 was interpreted as remission. Results: Patients remitting under ECT had significantly higher homocysteine (p < 0.001), S100B (p < 0.001), and procalcitonin (PCT) (p = 0.027) serum levels. On the contrary, serum levels of vitamin B12 (p < 0.001) and folic acid (p = 0.007) were significantly lower in remitters compared to those in nonremitters. Levels remained unchanged throughout the whole ECT course. Conclusions: Our findings indicate that lower levels of vitamin B12 and folic acid associated with higher levels of homocysteine, S100B, and PCT point to a subgroup of depressed patients sensitive to ECT. Due to the limited sample size, further studies are required to replicate our findings.
EVALuna2:211663